Acute effect of sacral neuromodulation for treatment of detrusor overactivity on urodynamic parameters. Issue 2 (5th December 2019) - Groenendijk, Ilse M.; Groen, Jan; Scheepe, Jeroen R.; Blok, Bertil F. M.
Abstract: Aim: The aim of this study is to evaluate the acute effects of sacral neuromodulation (SNM) on various urodynamic parameters. Methods: Patients with overactive bladder and detrusor overactivity (DO) who were planned for percutaneous nerve evaluation (PNE) were included. Directly after the PNE, a urodynamic study (UDS) was performed. The stimulation was turned off during the first UDS (UDS 1), and during the second filling cycle, stimulation was turned on (UDS 2). The UDS was followed by a test phase of 1 week and the bladder diaries were evaluated during an outpatient clinic visit. Primary outcome measures were the differences in UDS parameter values with SNM off and on. Results: Ten female patients were included in the study and completed the study protocol. Eight patients showed ≥50% improvement of symptoms following a test phase. There were no differences between UDS 1 and UDS 2 in the UDS parameters; bladder volume at first sensation, bladder volume at first DO, highest DO pressure, bladder capacity, maximum flow rate, and pressure at maximum flow rate. Discussion: None of the aforementioned urodynamic parameters was influenced by acute SNM in patients who responded to SNM. To the best of our knowledge, this is the first study investigating the acute effects of SNM on bladder function.